Molecular Detection and Genetic Characterization of Avian Leukosis Virus From Field Outbreaks in Bangladesh - Md. Golzar Hossain; Riman Pathan; SM Nazmul Hasan; Anandha Mozumder; Moslema Jahan Mou; Marjana Akter; Chandan Sikder; Riyan Al Islam Reshad; Roni Mia; Sukumar Saha; Tofazzal Islam; Sharmin Akter (Veterinary Medicine and Science)
ABSTRACT Avian leukosis is a significant viral disease affecting chicken populations globally, including Bangladesh, resulting in high mortality and morbidity rates and causing substantial economic losses in the commercial poultry industry. This study aimed to detect avian leukosis virus (ALV) during recent outbreaks in Bangladesh, utilising a molecular‐based approach. A total of 14 liver samples were collected from the suspected layer flocks in Bangladesh. The diagnosis of ALV infection in chickens was confirmed through necropsy, histopathological examinations, reverse transcription‐polymerase chain reaction (RT‐PCR), and sequence analysis. Gross observations revealed severe liver enlargement with scattered white nodules on the surface in the infected chickens. Histopathological observations showed the infiltration of huge mononuclear inflammatory cells in the periportal area of liver and microvesicular fatty degeneration and necrosis of some hepatocytes. RT‐PCR results identified three samples positive for the env gene of ALV. Sequence analysis of the env genes demonstrated high homology among the identified strains (97%–98%) and with reference strains (92%–96%) at the nucleotide level. The phylogenetic tree revealed close relatedness of the three identified strains to reference strains from India, USA, and China. Mutational analysis indicated several mutations throughout the envelope glycoprotein of the identified strains. Protein structure analysis showed minor changes in the hydrophobic region of the envelope protein of the identified strains. In conclusion, this study, the first detailed investigation in Bangladesh, contributes to understanding ALV epidemiology, highlights genetic diversity, and emphasises the necessity for further investigations and the implementation of effective control measures in the affected regions.